EROTISME DALAM TEKS SASTRA JAWA KUNA - Soeharto Mangkusudarmo (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2005)
Old Javanese literature which is well-known until the present is expressed in either prose or poetry (kakawin) . Old Javanese literature, kakawin, must comply with certain norms for example it must convey stones that portray battles, the beauty of nature and love . The portrayal of love expresses eroticism which radiates a sense of pornography. This is caused by the misinterpretation in appraising the erotic scenes . In discussing eroticism it is also important to consider the cultural background of the poet, sang kawi.